Informational need, institutional capacity, and court receptivity: interest groups and Amicus Curiae in State High Courts - Kane, Jenna Becker (2018)
Interest group participation in state courts of last resort has increased substantially over the past four decades, and the scope of this litigation activity has expanded to include a wider range of group participation. Despite the fact that organized interests increasingly recognize state high courts as legitimate policy venues, little is known about how interest groups choose the specific cases in which they participate. Beginning with the assumption that interest groups seek policy influence, this paper tests the hypothesis that groups strategically target cases that will best serve the policy and institutional interests of the group, while focusing group resources on cases and courts where they are most likely to be successful. Using an original dataset assembled from content analysis of more than 2,300 state supreme court decisions handed down between 1995 and 2010 and spanning three distinct areas of law$1 (Bproducts liability, environmental law, and free speech and expression$1 (Bthis paper investigates the case-level and court-level factors that attract interest group participation as amicus curiae in state high courts. - Reproduced.s
Keywords: Lobbying; Courts - United States